(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
Background: Allergy rhinitis (AR), a chronic disorder affecting the upper respiratory system, is the most prevalent allergy illness in the world. It has been reported that tobacco smoking reduces atopy and increases the occurrence of rhinitis symptoms. Aims of Study: Therefore, the aim of this study is to evaluate the association between exposure to active smoking and the prevalence of rhinitis in the adult Saudi population. Materials and Methods: A selfadministered questionnaire with closed-ended questions has been used in a cross-sectional quantitative investigation. Only authentic surveys that were given to Al-Kharj residents between May 2024 and March 2025 were included. We made use of 285 adults’ examination survey data. The diagnosis of AR was made using the following query: Have you ever been diagnosed with AR by a medical professional? Results: According to the results, a significant portion of the group (81.40%) had never tried traditional cigarettes. 53 people (18.59%) used it occasionally, frequently, or every day. In reference to the correlation between smoking cigarettes and AR, 71 participants (24.9%) had a medical diagnosis of AR at some point in their lives. Conclusion: In Saudi adults, cigarette smoking only was linked to AR. To fully understand the health risks associated with smoking, more long-term research is required.